2000
DOI: 10.1093/carcin/21.6.1149
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of potential chemopreventive agents on rat colon aberrant crypt formation and progression

Abstract: We assessed the effects of 78 potential chemopreventive agents in the F344 rat using two assays in which the inhibition of carcinogen-induced aberrant crypt foci (ACF) in the colon was the measure of efficacy. In both assays ACF were induced by the carcinogen azoxymethane (AOM) in F344 rats by two sequential weekly injections at a dose of 15 mg/kg. Two weeks after the last AOM injection, animals were evaluated for the number of aberrant crypts detected in methylene blue stained whole mounts of rat colon. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
104
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(116 citation statements)
references
References 24 publications
6
104
0
6
Order By: Relevance
“…14,19 Likewise, deguelin significantly decreased the number of ACF/colon during initiation by 50.9% (p Ͻ 0.05) and during promotion by 73.3% (p Ͻ 0.001) ( Table I). These results showed that the time of administration of either agent was not a significant (p Ͼ 0.05) factor.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…14,19 Likewise, deguelin significantly decreased the number of ACF/colon during initiation by 50.9% (p Ͻ 0.05) and during promotion by 73.3% (p Ͻ 0.001) ( Table I). These results showed that the time of administration of either agent was not a significant (p Ͼ 0.05) factor.…”
Section: Resultsmentioning
confidence: 91%
“…12 As a result, numerous studies have used the ACF assay to assess the efficacy of chemopreventive compounds. [13][14][15][16] Another important biomarker in the field of colon carcinogenesis is hex, a lysosomal enzyme active in normal colonic crypts yet decreased in up to 95% of ACF. 17 Decreased hex activity has been demonstrated in crypts with aberrant morphology (i.e., ACF) as well as in those that appear to have normal morphology.…”
Section: Abstract: Deguelin; Aberrant Crypt Foci; Hexosaminidase; Cfmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 Calcium-sensing receptor (CASR) is a member of the G protein-coupled receptor family. Extracellular Ca 2 þ and CASR serve as a first messenger system in controlling biological function.…”
mentioning
confidence: 99%